PERFORMANCE IMPROVEMENT STRATEGY TO INCREASE EMPLOYEE PRODUCTIVITY - Gresi Romantika Hasugian; Michael Olsen Siagia; Rahel Maretta Panjaitan; Sister Mille Yudarni Tafona’o; Muhammad Agung Anggoro (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2022)
This study aims to determine the Performance Improvement Strategy to Increase Employee Productivity at PTPN IV Berangir Plantation Business Unit. The type of research used is primary data. Our primary data are in the form of questionnaires and documentation on PTPN 4 Per.Berangin Rantau Prapat. This data collection is done by distributing questionnaires to respondents. This questionnaire was distributed to 33 respondents. This sampling technique used purposive sampling technique with the analytical tools used were Multiple Regression, T test, F test and the Coefficient of Determination of Hypothesis (R2). Classical Assumption Test is also used in this study, namely: Normality Test, Multicollinearity Test, Jji Heteroscedasticity. The results of this study indicate that the Performance Improvement Strategy to Increase Employee Productivity at PTPN IV Berangir Plantation Business Unit. Based on the coefficient of determination test, it can be seen that the remaining 1.4% is influenced by other variables not examined, namely 98.6%.